The Role of Professional Development on Teacher’s Performance: A Case Study Among Teachers in a Private School in Dubai - AlAbbassi, Mona (2020)
This study has been performed to determine the impact of professional development on the performance of teachers in context of private school sector of Dubai. The study intends to explore the impact of professional development and perception of professional development on the performance of the teachers. Based on the primary study model, the study uses a sample size of 150 individuals and a structured questionnaire was used to collect data. The simple random sampling approach has been used in this regard. It was hypothesized that there is a significant relationship between the performance of teachers, professional development, perception of professional development and importance of professional development. The key theories used in this case includes social development theory and organizational development theories in reference to the variables of the study. The major data analysis techniques used were correlation analysis, descriptive statistics, and the regression analysis. The findings of the study conclude that there is a strong and significant relationship between the variables of the study. The correlation analysis and the regression analysis indicate a strong association between the variables based on significant correlations and coefficient of determination. Based on the findings of the study, it has been recommended that certain standards should be developed by the institutions that promote the level of professional development among staff members can be increased. In addition to it, the outcomes of the study are constrained due to the sample size, data collection approach, lack of studies in that particular research area and the scope of the research. The study is expected to add significantly in the existing body of knowledge due to its practical implications in this regard. This study can be replicated in a different sector of a country or for a different population and a comparison can be drawn that which sector needs the resources of professional development.